Inclusive health for people with disabilities in Chile: a national health system assessment - Danae Rodríguez Gatta; Constanza Piriz Tapia; Elvira Tagle Schmidt; Jimena Luna Benavides; Daniel Vivar Jara; Rodrigo Moreno Celis; Gonzalo Tobar Carrizo; Judit Vilaró Cáceres; Phyllis Heydt; Lena Morgon Banks; Hannah Kuper (Health Research Policy and Systems)
Abstract Background Globally, one in six people have disabilities. They often experience health inequities and many of them arise from system-level failures. This study aimed to assess the inclusion of people with disabilities in the health system of Chile and define recommendations for improvement on the basis of the evidence. Methods A health system assessment was conducted between June and November 2023 following the Missing Billion Disability-Inclusive Health Systems Framework and System Level Assessment Toolkit. The assessment was led by the Ministry of Health and conducted by a task team, including organizations of people with disabilities. Mixed methods were used to collect data on nine system-level and service delivery components for a set of 33 indicators, including through a health policy review, systematic review, key informant interviews and a scoping review. Scores were assigned to indicators, components and the overall health system. With this assessment, key recommendations were developed and agreed upon on the basis of a prioritization analysis of impact and feasibility during workshops. Results The Chilean health system was assessed to have a low progress towards disability-inclusive health. Among system-level components, intermediate progress has been made in governance, health financing and data and evidence. However, progress in leadership on disability seems low. Among service delivery components, the accessibility of health facilities and rehabilitation and assistive technology showed the best results. However, there were notable gaps in the autonomy and awareness and ability to afford care by people with disabilities, and the capacity of human resources to support this group. The task team defined priority actions in governance, leadership, and human resources. Conclusions Short-term actions for the country should involve foundational governance on inclusive health, strengthened leadership of people with disabilities, and mandatory training of healthcare workers to improve healthcare access among this population. Future reassessments should be conducted to monitor and evaluate progress on effective healthcare coverage and health status among people with disabilities.